Sorghum grain as the only protein source in all-concentrate heifer finishing rations: Two levels of urea in an all-concentrate ration - E.F. Smith; D. Richardson; C.L. Drake; B.E. Brent (Kansas Agricultural Experiment Station Research Reports, 1968)
Tests reporting on sorghum grain as the only protein source in a diet for finishing cattle are reported in Kansas Agr. Expt. Station Bulletins 493 and 507 and on page 24 in this bulletin. The three rations fed are show in table 10. The sorghum grain was obtained as needed at a local elevator, mixed with other ration ingredients at the Animal Husbandry elevator and delivered, usually in 2000 lb. loads to the self feeders when needed.
Keywords: Cattlemen& #x27; s Day; 1968; Report of progress (Kansas State University. Agricultural Experiment Station); 518; Beef; Sorghum grain; Protein; All-concentrate ration; Urea